A mechanism for water splitting and hydrogen absorbing functions of metal–oxide layered hydrogen storage materials studied by means of ion beam analysis. (16th January 2014) - Morita, Kenji; Tsuchiya, Bun
<x xml:space="preserve">Abstract</x> This review describes a study of catalytic functions of water splitting at the surface and hydrogen gas emitting from the bulk of metal–oxide layered materials as well as hydrogen storage materials as its application by means of the ion beam analysis techniques. First are described a microscopic model for water splitting at the oxide surface and mass balance equations for hydrogen atoms in the bulk. The latter is a mathematical expression of a one‐way diffusion model proposed for an anomalous isotope effect in D–H and H–D replacements of both deuterium (D) implanted into perovskite oxide ceramics by protium (H) in H2O vapour and the vise versa. The latter model brings about finding of catalytic functions of water splitting at the surface and hydrogen gas emitting from the bulk. Second, experimental results on the anomalous isotope effect are presented and the D–H replacement rates are described in detail. Subsequently are shown results on H2 gas emission measured with a Bach method, which give a clear evidence for the water splitting and hydrogen gas emitting catalytic functions of the oxide surface. Finally, we present experimental data on the hydrogen absorption and emission characteristics of the metal–oxide layered hydrogen storage materials as an application of the water splitting and hydrogen absorbing catalysts. Copyright © 2014 John Wiley & Sons, Ltd.